Effect of anthropogenic forcing on increased winter precipitation in Southeast Asia from 1979 to 2014 - Dong, Zizhen; Yang, Ruowen; Cao, Jie; Wang, Lin (Frontiers in Environmental Science, 2023)
Observations indicate that the winter precipitation over Southeast Asia (SEAP) shows significantly increased trends from 1979 to 2014, which can be partly reproduced under the historical all-forcing simulations from the 12 Coupled Model Intercomparison Project Phase 6 (CMIP6) climate models. By analyzing separate external forcings run with the Detection and Attribution experiments, we find that the effects of anthropogenic forcing rather than natural variation play a primary role in driving the increasing of SEAP trends simulated in the historical all-forcing experiments. Further analysis indicate that the observed increasing trend is closely associated with the decadal shift of the Southeast Asian precipitation after the mid-1990s, which could be also driven by anthropogenic forcing to some extent. Anthropogenic forcing can favor a La Niña-like pattern of sea surface temperature (SST) warming in the tropical Pacific and result in the decadal increase of SEAP via the enhanced zonal SST gradient and the Pacific Walker circulation. This study thus provides some evidence of the impacts of anthropogenic forcing to drive recent changes in the winter SEAP.